How Can Donors Help Build Global Public Goods in Health? - Das Gupta, Monica; Gostin, Lawrence (2012)
Aid to developing countries has largely neglected the population-wide health services that are core to communicable disease control in the developed world. These mostly non-clinical services generate "pure public goods" by reducing everyone's exposure to disease through measures such as implementing health and sanitary regulations. They complement the clinical preventive and treatment services which are the donors' main focus. Their neglect is manifested, for example, in a lack of coherent public health regulations in countries where donors have long been active, facilitating the spread of diseases such as avian flu. These services can be inexpensive, and dramatically reduce health inequalities. Sri Lanka spends less than 0.2% of GDP on its well-designed population-wide services, which contribute to the country's high levels of health equity and life expectancy despite low GDP per head and civil war. Evidence abounds on the negative externalities of weak population-wide health services. Global public health security cannot be assured without building strong national population-wide health systems to reduce the potential for communicable diseases to spread within and beyond their borders. Donors need greater clarity about what constitutes a strong public health system, and how to build them. The paper discusses gaps in donors' approaches and first steps toward closing them.